2009
DOI: 10.1603/022.038.0614
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Invasive and Native Ant on a Field Population of the Black Citrus Aphid (Hemiptera: Aphididae)

Abstract: Invasive ants often enter into facultative mutualisms that frequently lead to outbreaks of the hemipteran partner. Native ants may also enter into similar mutualisms but often these do not lead to outbreaks. However, field studies comparing the impact of an invasive and native ant on a honeydew-producing hemipteran are lacking. We monitored numerical changes of the black citrus aphid, Toxoptera aurantii, tended by adjacent colonies of the invasive Argentine ant, Linepithema humile, and the endemic odorous hous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Ceroplastes scale abundance in our screenhouse (c. 24 ± 3 scales per plant) was much lower than phloem-feeder infestations that reduce plant growth or fitness in other systems (up to 200 aphids per plant, Powell et al, 2009;150-250 aphids per plant, Brightwell & Silverman, 2010; up to 1,000 scales per plant, Kulikowski II, 2020).…”
Section: P Megacephala and Native Ceroplastes Scales Perhaps Becausementioning
confidence: 68%
“…Ceroplastes scale abundance in our screenhouse (c. 24 ± 3 scales per plant) was much lower than phloem-feeder infestations that reduce plant growth or fitness in other systems (up to 200 aphids per plant, Powell et al, 2009;150-250 aphids per plant, Brightwell & Silverman, 2010; up to 1,000 scales per plant, Kulikowski II, 2020).…”
Section: P Megacephala and Native Ceroplastes Scales Perhaps Becausementioning
confidence: 68%
“…Schwartzberg et al (2010) showed that the biomass of the aphid Aphis glycines Matsumura (Hemiptera: Aphididae) increased when the aphids were assisted by ants of the species Lasius neoniger Emery (Hymenoptera: Formicidae). The increases in populations of Toxoptera aurantii (Boyer de Fonscolombe) (Hemiptera: Aphididae) (Powell et al 2009), Aphis gossypii Glover, and Myzus persicae (Sulzer) (Hemiptera:Aphididae) (Powell and Silverman 2010) were greater when these aphids were tended by L. humile and Tapinoma sessile (Say) (Hymenoptera: Formicidae), compared with nontended populations.…”
Section: Discussionmentioning
confidence: 99%
“…The vast spread and high abundance of invasive species seriously threatens native ecosystems as well as affecting biodiversity conservation worldwide ( Human and Gordon, 1996 ; Tsutsui et al, 2000 ; Suarez and Case, 2002 ; Powell et al, 2009 ; Gao and Reitz, 2017 ; Pyšek et al, 2017 ). For example, the Argentine ant ( Linepithema humile ), which is on the IUCN (International Union for Conservation of Nature) list of the 100 world’s worst invasive species, is one of the most widely-distributed invasive pests in six continents and the Pacific islands, including New Zealand, Hawaii, and Japan ( Lowe et al, 2000 ; Giraud et al, 2002 ; Suhr et al, 2010 ; Van Wilgenburg et al, 2010 ; Ward et al, 2010 ; Mothapo and Wossler, 2011 ; Sato et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%